FUTURE EDUCATION: PARADIGM, SKILLS, DISRUPTIVE INNOVATION, LIFE BASE LEARNING AND FUTURE TEACHER - Agussalim; Wahyuni; Sukardi; Ahmad Yani; Fitriani (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2023)
This article aims to explore the thinking of Future Education: New Education Paradigm, Future Learning Skills, Disruptive Innovation, Life Based Learning, and Future Teachers. The article uses the library research method. The results of the study found that the world of education must transform itself with existing changes while remaining guided by values and morals. Paradima shift towards capability development, life based learning/real word learning, learner as a human being, hautagogy/self-directed-learning, multi-disciplinary curriculum, and job creator. Skill needs include critical thinking and creativity, communicativeness and collaboration, and information and communication technology skills and morality. Disruptive innovation is characterized by digital technology making learning more flexible. Life Based Learning focuses on developing capabilities and life skills. Future teachers must be the best sons and daughters and be inspirational and have multi-skills.